1993
DOI: 10.1073/pnas.90.10.4394
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal protein S15 from Escherichia coli modulates its own translation by trapping the ribosome on the mRNA initiation loading site.

Abstract: From genetic and biochemical evidence, we previously proposed that S15 inhibits its own translation by binding to its mRNA in a region overlapping the ribosome loading site. This binding was postulated to stabilize a pseudoknot structure that exists in equilibrium with two stemloops. Here, we use "toeprint" experiments with Moloney murine leukemia virus reverse transcriptase to analyze the effect of S15 on the formation of the ternary mRNA-30S-tRNAmIet complex. We show that the binding of the 30S subunit on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(114 citation statements)
references
References 18 publications
7
105
2
Order By: Relevance
“…Binding of EcS15 to the pseudoknot has been shown to trap the 30S subunit onto the mRNA in a non-productive initiation complex. 13,17 The structures of the entrapped and productive initiation complexes were recently solved by cryo-electron microscopy. 17 In the active complex, the unpaired mRNA is positioned in the classical mRNA channel and promotes the formation of the codon-anticodon interaction in the peptidyl-tRNA (P-) site.…”
Section: Plasticity Of Mrna-regulatory Protein Recognition In Translamentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of EcS15 to the pseudoknot has been shown to trap the 30S subunit onto the mRNA in a non-productive initiation complex. 13,17 The structures of the entrapped and productive initiation complexes were recently solved by cryo-electron microscopy. 17 In the active complex, the unpaired mRNA is positioned in the classical mRNA channel and promotes the formation of the codon-anticodon interaction in the peptidyl-tRNA (P-) site.…”
Section: Plasticity Of Mrna-regulatory Protein Recognition In Translamentioning
confidence: 99%
“…2C). 13 Such a structural motif displays diverse functions in the regulation of protein synthesis in bacteria as well as in viruses and eukaryotes. 10 Figure 2. mRNA-protein induced-fit allows translation regulation via different mechanisms: the example of ribosomal protein S15 autoregulation in different bacteria.…”
Section: Plasticity Of Mrna-regulatory Protein Recognition In Translamentioning
confidence: 99%
“…In Escherichia coli, S15 recognizes a pseudoknot structure folded within its own mRNA [25][26][27], rather than the three-way junction architecture associated with thermophilic bacteria. Although the ribosome can interact with mRNA already bound to S15, it cannot initiate translation in E. coli [28]. A long-awaited cryo-electron microscopy study [29] showed that in the stalled ribosome, S15 positions itself along the mRNA pseudoknot, and the S15-mRNA complex is nested on a special platform of the small ribosomal subunit (Figure 3b).…”
Section: Recognition Of Three-dimensional Mrna Structures By Proteinsmentioning
confidence: 99%
“…In a number of cases their expression is regulated through a feedback mechanism, in which one or more protein products of a given operon acts as a regulator (Babitzke et al 2009). Upon saturation of the binding site on a ribosomal RNA (rRNA), a regulator-protein binds to its own mRNA, frequently within the 5 ′ untranslated region (5 ′ UTR) (Nomura et al 1980;Freedman et al 1987; Thomas and Nomura 1987;Portier et al 1990;Philippe et al 1993;Guillier et al 2002). This interaction inhibits translation initiation by occlusion of a ribosome binding site or ribosome entrapment, permitting maintenance of the balance of r-protein and rRNA levels.…”
Section: Introductionmentioning
confidence: 99%